PENGARUH FITUR ROBO ADVISOR DAN MINIMAL TOP UP TERHADAP MINAT INVESTASI REKSADANA (STUDI KASUS PADA APLIKASI BIBIT DAN BAREKSA) - Ariyanti, Septi Dwi; Pangestuty, Farah Wulandari (Contemporary Studies in Economic, Finance and Banking, 2023)
The capital market is a sector that has an important role in economic development because the capital market performs a dual function, namely as a medium for companies to obtain capital as well as a medium for the public to invest. It can be seen that the number of investors has increased every year. However, this increase is in contrast to the low level of financial literacy and inclusion in the capital market. This study aims to determine the effect of the robo advisor feature and minimum top up on mutual funds investing intention by the people of East Java in the Bibit and Bareksa applications. With a population of 100 users of the Bibit and Bareksa applications in East Java, a total sample of 80 people and using the logistic regression method, the results show that the robo advisor feature and minimum top up have a significant effect on mutual funds investing intention so it can be concluded that these two variables can increase opportunities and contribute to investing intention. Keywords: Bibit and Bareksa Applications; Minimum Top Up; Mutual Funds Investing Intention; Robo Advisor Feature.